(untitled) (CIPEEX, 2025)
The aim of this study was to synthesize Ascaris lumbricoides infection, covering the diagnosis, treatment, and epidemiology of ascariasis. Ascaris lumbricoides is the etiological agent of ascariasis, commonly known as roundworm infection. It is a nematode classified as a geohelminth due to its soil-dependent life cycle stage. The infection is transmitted via fecal-oral routes, often through contaminated food or water. The larval egg must contain an infective L3 larva, which develops in the soil from the L1 stage through L2, under favorable conditions of temperature, oxygen, and humidity. The egg hatches in the stomach and the larva migrates to the small intestine, enters the bloodstream, and eventually reaches the lungs for further development from L3 to L4. After ascending the respiratory tract and being swallowed, the larva returns to the small intestine, where it matures into male and female adults, copulates, and releases eggs through feces. Diagnosis is made by fecal examination, typically using the Hoffman, Pons, and Janer (HPJ) method, which reveals three egg types: fertile with nipple, decorticated fertile, and infertile eggs. Clinical manifestations vary, ranging from asymptomatic cases to abdominal pain and respiratory symptoms. Severe infections may lead to intestinal obstruction, malnutrition, cognitive deficits, and, in rare cases, extraintestinal migration, where worms exit through the mouth or nose. Children in areas with inadequate sanitation are the most vulnerable due to hand-to-mouth habits and immature immune systems. Globally, around 22% of the population is affected by ascariasis, with 10% of these cases in Latin America. Although treatable, ascariasis poses significant public health challenges, particularly in areas with inadequate sanitation.